Mortars with phase change materials - Part II: Durability evaluation - Cunha, Sandra Raquel Leite (2015)
The industry of construction is responsible for the high consumption of raw materials, energy and waste production. As such, it becomes imperative to develop and study new constructive solutions with greater sustainable value. The mortars with incorporation of phase change materials (PCM) have the ability to regulate the temperature inside buildings, contributing to the thermal comfort and reducing the use of heating and cooling equipment, using only the energy supplied by the sun. However, the incorporation of phase change materials in mortars modifies its characteristics. The main focus of this study was the durability of mortars with PCM incorporation based in different binders. The binders studied were aerial lime, hydraulic lime, gypsum and cement. For each type of binder, different mortars were developed with different content of PCM. The proportion of PCM studied was 0% and 40% of the mass of the sand. It was possible to observe that the incorporation of PCM in mortars caused differences in properties such as water absorption by capillarity, water absorption by immersion and degradation after freeze-thaw cycles.